The Medicinal Properties of Paullinia pinnata Linn. Leaves - Oluwatoyin Adenike Adeyemo-Salami (International Journal of Phytomedicine, 2020)
Paullinia pinnata is a plant introduced to tropical Africa and has been reported to be useful in folkloric medicine. Different medicinal potentials of the leaves have been investigated some of which have corroborated reports in traditional medicine. Compounds have been isolated from extracts of the leaves which have been shown to have medicinal value. These compounds are from different classes of secondary metabolites including tannins, flavonoids and alkaloids. Fatty acids have also been shown to be present. This report is set to enumerate the traditional use of the leaves of P.pinnata and research findings already documented.